A galeria de presidentes da Associação Bahiana de Medicina (ABM):: lugar de memória - Ramos, Tassila Oliveira; Silva, Silvana Pereira da (Revista Fontes Documentais, 2023)
This study is the result of research that supports the creation of the Memory Center of the Bahiana Association of Medicine (ABM). In this initial phase, we will give a brief overview of the trajectory of the Bahiana Association of Medicine (ABM), contextualizing the importance of its collections, specifically that of the Gallery of Presidents as a place of memory and a collection of health in the State of Bahia. Based on the reflections of the theoretical-descriptive study of a memorial site as it contains materialized proven and registered memory of important personalities of social and collective relevance